Effect of dietary probiotics and prebiotics on the performance of broiler chickens - Al-Khalaifa, H; Al-Nasser, A; Al-Surayee, T; Al-Kandari, S; Al-Enzi, N; Al-Sharrah, T; Ragheb, G; Al-Qalaf, S; Mohammed, A (Poultry science, 2019)
The prolonged use of antibiotics has led to the development of resistant bacteria and also led to accumulation of antibiotic residue in the poultry feed, this ultimately led to the prohibition of antibiotics as growth enhancers in animal production. Thus, there was a dire need for alternate sources to help in poultry production. Recently, probiotics and prebiotics claimed to be effective alternatives to antibiotics in the poultry. The objective of this study is to investigate the effect of different probiotics and prebiotics on the performance of broilers. The study involved 2 broiler cycles, 1 during winter and 1 during summer with a total of 425 1-day-old Cobb 500 broiler chicks for each cycle. They were allotted to 5 experimental treatments. The probiotics were Bacillus coagulans (1 g/kg dried culture) and Lactobacillus (1 g/kg dried culture of 12 commercial strains). The prebiotics included fructo-oligosaccharides (FOS) (5 g/kg) and mannan-oligosaccharide (MOS) derived from Saccharomyces cerevisiae (5 g/kg). The results showed that there was no effect of the different probiotics and prebiotics on the production performance of broilers. There was increased weight of the thymus in the control group. In cycle 1, the panelists indicated that the smell, color, taste, and texture of the cooked meat were acceptable, and that there were no significant differences between the different groups. There was no significant effect of the different diets on the biochemical parameters of the blood among the experimental groups at 3- and 5-wk of age. Phytohaemaglutinin test showed that dietary FOS and MOS induced higher cellular response than the other treatments (P = 0.04) in the first cycle. In the second cycle, the results revealed that dietary FOS induced higher cellular response than the other treatments (P = 0.019). The used experimental treatments have a positive effect on microbial count in 5-week-old broilers. There was no Salmonella sp. recorded using the experimental treatments in the first cycle, and the growth of E. coli was reduced significantly. In the second cycle, all treatments in 3-week-old broilers did not affect the count of both lactic acid bacteria (LAB) and E. coli. At 5-week-old of the same cycle, the bacterial count of E. coli increased even with control, whereas Salmonella growth was inhibited. The pH value was driven toward acidity in all of the treatments. Probiotics and prebiotics can be used in chicken feed safely and without any adverse effects on the productive parameters and immune status of the flock.